Relationship between Positive Self-esteem, Gender and Social Anxiety among College Students during the Pandemic (2024)
Objective: This study aimed to analyze the association between positive self-esteem, gen-der, and social anxiety levels of college students during the second year of the COVID-19 pandemic.Materials and methods: The research was developed based on a quantitative paradigm, through a cross-sectional, correlational–causal, and non-experimental design. The sample consisted of 212 university students who were assessed using the Rosenberg Self-esteem Scale and the Social Anxiety Questionnaire for Adults. Descriptive analyses of the study variables were performed, and the results were compared according to the gender of the participants. Furthermore, binary logistic regression was employed to assess the associa-tion between positive self-esteem, gender, and social anxiety levels.Results: There was a significant negative association between positive self-esteem and anxiety. Two indicators of positive self-esteem significantly and negatively predicted eleva-ted levels of social anxiety. Additionally, being female was associated with a higher risk of elevated levels of social anxiety. This model explained 16.4 % (Cox and Snell R2) and 28 % (Nagelkerke R2) of the total variance, respectively.Conclusion: These results highlight the importance of promoting positive self-esteem as a protective factor for mental health during crisis situations. This finding has practical im-plications for higher education institutions. By identifying the factors that contribute to positive self-esteem and reduced social anxiety among college students, institutions can develop targeted interventions and support programs to enhance students’ well-being and academic success. Moreover, they revealed the need to address the development of support strategies in educational settings from the gender perspective.